Smoke, mirrors, and murder [compact disc, abridged] : and other true cases - Rule, Ann (Rule, Ann. Ann Rule's crime files, 2013)
A compilation of real-life crime stories includes the tales of a counterfeit priest, a serial rapist, a victim burned beyond recognition, and a con artist whose activities lead to murder.